Energy Valuation Methods for Biofuels in South Florida: Introduction to Life Cycle Assessment and Emergy Approaches - J. Van Treese, II; Edward A. Hanlon; N. Y. Amponsah; J. L. Izursa; J. C. Capece (EDIS)
This 5-page fact sheet gives an overview of two methods for evaluating energy transformations in biofuels production. The Life Cycle Assessment approach involves measurements affecting greenhouse gases, which can be linked to the energy considerations used in the Emergy Assessment. Although these two methods have their basis in energy or greenhouse gas emission evaluations, their approaches can lead to a reliable judgment regarding a biofuel process. We can use them to evaluate the economic environmental component of a biofuel process, and decide which biofuel processes favor sustainability. The intended audiences of this publication are growers, researchers, students, and any other readers interested in agriculture and ecology. Written by J. Van Treese II, E. A. Hanlon, N. Y. Amponsah, J. L. Izursa, and J. C. Capece, and published by the UF Department of Soil and Water Science, March 2013.